CONSIDERATION OF FISH STOCK DYNAMICS FOR THE IMPLEMENTATION OF FISHING PRECISION POLICY - Sondita, Muhammad Fedi Alfiadi; Darmawan; Purbayanto, Ari; Zulkarnain; Simbolon, Domu; Wahju, Ronny Irawan (Departemen PSP IPB, 2025)
The Government of Indonesia is implementing a Measured Fishing policy to ensure the sustainable utilization of fishery resources. However, 88% of fish stocks are currently in fully fished (35%) or overfished (53%) condition, which hinders the attainment of maximum sustainable yield (MSY). This study aims to examine the influence of initial biomass (B₀) and annual harvest rate (Yₜ) on the sustainability of annual catch (Cₜ) and remaining biomass (Bₜ) using a logistic differential equation (LDE) model. Simulations were conducted across nine fishery models, combining three levels of B₀ and three levels of Yₜ, under assumptions of carrying capacity (K) of 1000 tons and a hipothetical fish biomass with intrinsic growth rate (r) of 0.05. Results indicate that the ratio of Yₜ to the current sustainable yield (SYₜ) is the primary determinant of stock sustainability and fishery longevity, regardless of B₀. This finding suggests that total allowable catch (TAC) should not be based solely on MSY, but rather adjusted according to SYₜ, while also incorporating precautionary principles and stock recovery strategies. This approach offers a more adaptive and realistic policy framework aligned with current stock conditions and supports the long-term sustainability of capture fisheries. Key words: biomass models, fish stocks, precision fishing, sustainable potency, TAC